Peer status beyond adolescence : Types and behavioral associations - Rüschoff, Britta [Verfasser]; Dijkstra, Jan Kornelis [Verfasser]; Veenstra, René [Verfasser]; Lindenberg, Siegwart [Verfasser] (My University, 2015)
"This study investigates the types and behavioral associations of peer status in schoolbound young adults in the Netherlands. We argue that adolescent peer popularity and its link with aggressive and norm-breaking behavior result from adolescents' desire to create an image of maturity among their peers. We expect that in young adults who are approaching working life, peer status is defined by affective measures of status and prosociality rather than adverse behaviors. Analyses revealed a three cluster solution of (1) liked, (2) liked-popular and (3) neutral members of the peer group, showing that status is primarily defined by being well-liked, though popularity remains relevant. Status was primarily associated with prosocial behavior, especially for females. Peer status in young males remained associated with overt aggressive behavior." (authors' abstract; BIBB-Doku)
Keywords: P 1.1 Jugendliche; G 2.4 Sozialer Wandel; G 1.3.2.2 Übergänge; I 2.2.1 Westeuropa; Jugendlicher; Junger Erwachsener; Peer group; Sozialer Status; Aggression; Verhaltensforschung; Berufseinmündung; Niederlande